Image-Based Analysis of Tumor Localization After Intra-Arterial Delivery of Technetium-99m-Labeled SPIO Using SPECT/CT and MRI - In Joon Lee MD, PhD; Ji Yong Park MS; Young-il Kim MD, PhD; Yun-Sang Lee PhD; Jae Min Jeong PhD; Jaeil Kim BS; Euishin Edmund Kim MD, PhD; Keon Wook Kang MD, PhD; Dong Soo Lee MD, PhD; Seonji Jeong MD; Eun Jeong Kim BS; Young Il Kim MD, PhD; et al. (Molecular Imaging, 2017)
The aim of this study is to evaluate the localization of 99m Tc-labeled dextran-coated superparamagnetic iron oxide (SPIO) nanoparticles to the liver tumor using image-based analysis. We delivered 99m Tc-SPIO intravenously or intra-arterially (IA) with/without Lipiodol to compare the tumor localization by gamma scintigraphy, single-photon emission computed tomography (SPECT), and magnetic resonance imaging (MRI) in a rabbit liver tumor. The gamma and SPECT image-based analysis shows that the uptake ratio of the tumor to the normal liver parenchyma is highest after delivery of 99m Tc-SPIO with Lipiodol IA and that well correlates with the trend of the signal decrease in the liver MRIs. Intra-arterial delivery of SPIO with Lipiodol might be a good drug delivery system targeting the hepatic tumors, as confirmed by image-based analysis.